Job satisfaction of midwives: a literature review - Nedvědová, Daniela; Dušová, Bohdana; Jarošová, Darja (Central European Journal of Nursing and Midwifery, 2017)
Aim:The aims of the literature review were to identify andanalyzefactors affecting job satisfaction of midwives. Design:Aliterature review.Methods: Included in the literature review were full texts of papers published in English language from 1990 to 2014. The search for relevant data was performed using the electronic databases CINAHL, Medline, Science Direct and Wiley Online Library. From a total of 43 studies found, 11were analyzed as quantitative studies that fulfilled the specified criteria. Results: Job satisfaction of midwives is affected by a lack of support from the management of healthcare facilities, low salary, understaffing, insufficient time for professional activities, work-family imbalance, high workload, physical demands, inadequate professional development, working environment, stress and low autonomy at work. Midwives showed signs ofexhaustion, fatigue, hostility and depression, contributing to job turnover. Conclusion:The literature review presents the factors influencing job satisfaction of midwives. This is affected by many variable determinants, which create a feeling of job satisfaction of midwives, but can also lead to job dissatisfaction and, consequently, high turnover.
Keywords: babictví; porodní asistentky; Nurse Midwives; lidé; fluktuace zaměstnanců; Personnel Turnover; pracovní uspokojení; Job Satisfaction; Humans; Information Storage and Retrieval; Midwifery; motivace; ukládání a vyhledávání informací; Motivation